The impact of socioeconomic status and sleep quality on the prevalence of multimorbidity in older adults - Xue, Benli; Xue, Yaqing; Dong, Fang; Zheng, Xiao; Shi, Lei; Xiao, Shujuan; Zhang, Jiachi; Ou, Weiyan; Wang, Qi; Zhang, Chichen (Frontiers in Public Health, 2022)
Introduction Multimorbidity has become a global public health concern that can cause serious damage to the health status of older adults. This study aimed to investigate the impact of socioeconomic status (SES) and sleep quality on the prevalence of multimorbidity in older adults, thus providing a reference for reducing the risk of the prevalence of multimorbidity and improving the health of older adults. Methods A multi-stage random sampling method was used to conduct a questionnaire survey on 3,250 older adults aged 60 years and above in Shanxi Province, China. The chi-square test and multiple logistic regression models were used to analyze the association of SES and sleep quality with the prevalence of multimorbidity of older adults. Results The prevalence of multimorbidity was 30.31% in older adults aged 60 years and above in Shanxi Province, China. After adjusting for confounders, very low SES (OR = 1.440, 95% CI: 1.083–1.913) and poor sleep quality (OR = 2.445, 95% CI: 2.043–2.927) were associated with the prevalence of multimorbidity. Older adults with low SES and poor sleep quality had the highest risk of the prevalence of multimorbidity (OR = 3.139, 95% CI: 2.288–4.307). Conclusions SES and sleep quality are associated with the prevalence of multimorbidity in older adults, and older adults with lower SES and poorer sleep quality are at higher risk for the prevalence of multimorbidity.